Training on Calculating Cost of Goods Sold and Simple Bookkeeping for PKK Members Engaged in MSMEs in Pringwulung Hamlet, Sleman - Ratri Paramitalaksmi; Martinus Budiantara (Mattawang: Jurnal Pengabdian Masyarakat, 2025)
The main problems faced by the community partners, namely the PKK members who run micro-businesses in Padukuhan Pringwulung, Sleman, are the lack of financial budgeting systems, inadequate financial records, and inability to calculate Cost of Goods Sold (COGS). This community service aims to enhance their skills in preparing budgets, maintaining simple bookkeeping, and calculating COGS independently. The methods used include socialization, counseling, workshops, and hands-on practical sessions using case studies tailored to participants’ business types. A total of 80 participants were actively involved in the initial training, followed by mentoring through site visits and an online communication group. Evaluation was conducted through pre–post tests, practice observation, and satisfaction questionnaires. The results indicate improvement in hardskills: 80% of participants can calculate COGS, and 70% record transactions consistently for at least three weeks. Softskills also improved, including increased awareness of financial management and entrepreneurial motivation. This program positively impacts the economic capacity of families through better administrative practices.